Transurethral intraprostatic injection of botulinum neurotoxin type A for the treatment of chronic prostatitis/chronic pelvic pain syndrome: results of a prospective pilot double‐blind and randomized placebo‐controlled study. (25th May 2015) - Falahatkar, Siavash; Shahab, Elaheh; Gholamjani Moghaddam, Keivan; Kazemnezhad, Ehsan
<x xml:space="preserve">Abstract</x> Objective To evaluate the effect of botulinum neurotoxin type‐A (BoNT‐A) on chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) refractory to medical therapy. Materials and Methods Between November 2011 and January 2013, 60 men aged ≥18 years with CP/CPPS, and with National Institutes of Health Chronic Prostatitis Symptom Index (NIH‐CPSI) scores ≥10 and pain subscale scores ≥8, who were refractory to 4–6 weeks' medical therapy, underwent transurethral intraprostatic injection of BoNT‐A or normal saline in a prospective pilot double‐blind randomized study. The patients' NIH‐CPSI total and subscale scores, American Urological Association (AUA)‐symptom score (SS), visual analogue scale (VAS) and quality of life (QoL) scores and frequencies of diurnal and nocturnal urination were evaluated and compared at baseline and at 1, 3 and 6 months after injection and also were compared between the two groups. Results A total of 60 consecutive patients were randomized to a BoNT‐A (treatment) or normal saline (placebo) group. In the treatment group at the 1‐, 3‐ and 6‐month evaluation the NIH‐CPSI total and subscale scores, and the AUA‐SS, VAS and QoL scores, along with frequencies of diurnal and nocturnal urinations, had significantly improved compared with baseline values (P < 0.05). By contrast, in the placebo group, none of these values showed improvement and the values were significantly different from those in the treatment group. Although the differences between the two groups in AUA‐SS and frequencies of nocturnal urination were not significant at 1‐month follow‐up, repeated‐measure analysis showed significant improvement in each of these values over the entire follow‐up period in the treatment group. The most prominent improvement was related to the pain subscale score, which decreased by 64.76, 75.63 and 79.97% at 1, 3 and 6 months after treatment compared with baseline, followed by the VAS score, which decreased by 62.3, 72.4 and 82.1% at each follow‐up, respectively. Only two patients developed mild transient gross haematuria, which was managed conservatively. Conclusions Transurethral intraprostatic BoNT‐A injection maybe an effective therapeutic option in patients with CP/CPPS as it reduces pain and improves QoL.